Variance - Correlation analysis in the exploration of hydrothermal (fluidogenous) deposits using surface gamma-ray spectrometry; Journal of Applied Geophysics; Vol. 159 - Sobolev I. S. Igor Stanislavovich; Orekhov A. N. Aleksandr Nikolaevich; Bratec T. Tatiana; Rikhvanov L. P. Leonid Petrovich; Soboleva N. P. Nadezhda Petrovna (2018, 2018)
Title screen